2023
DOI: 10.3390/ma16062431
|View full text |Cite
|
Sign up to set email alerts
|

The Charge Distribution, Seebeck Coefficient, and Carrier Concentration of CuCr0.99Ln0.01S2 (Ln = Dy–Lu)

Abstract: The atom oxidation states were determined using the binding energies of the core S2p-, Cu2p-, Cr2p-, and Ln3d-levels in CuCr0.99Ln0.01S2 (Ln = Dy–Lu) solid solutions. The charge distribution on the matrix elements (Cu, Cr, and S) remained unaffected after cationic substitution. The sulfur atoms were found to be in the S2− oxidation state, the copper–Cu+, and the chromium–Cr3+. The cationic substitution of the initial CuCrS2-matrix occurred via the isovalent mechanism. The obtained results were compared with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(30 citation statements)
references
References 41 publications
7
22
1
Order By: Relevance
“…. .Lu) compounds were synthesized using high-purity commercial metal oxides via the previously reported sulfidation route [34]. The samples were found to be single-phase and isostructural to the initial CuCrS 2 -matrix [41].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…. .Lu) compounds were synthesized using high-purity commercial metal oxides via the previously reported sulfidation route [34]. The samples were found to be single-phase and isostructural to the initial CuCrS 2 -matrix [41].…”
Section: Methodsmentioning
confidence: 99%
“…The XRD data evidencing the cationic substitution of the chromium atoms with lanthanides and the study of the doping mechanism were reported previously [35,36,[39][40][41]. The ceramic samples were prepared by compressing the synthesized powder samples under uniaxial pressure in a vacuum [34]. The measurements of the Seebeck coefficient of the CuCr 0.99 Ln 0.01 S 2 compounds were carried out using the original experimental setup described in detail in [32,34,36].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations